Variation in yield components and bioactive contents of black cumin seeds (Nigella sativa L.) with application of animal manures in ultisol lowland of Bengkulu - Herlina Herlina; Evi Andriani (Universitas Prof. Dr. Hazairin SH, 2020)
Black cumin (Nigella sativa L) is known as herbal medicine that grows in subtropical regions and spreads from Asia to Europe. Plant parts that are used are seeds that contain bioactive compounds such as thymoquinone and thymol. Information about the growth and production from Indonesia is still limited. Therefore it is necessary to develop efforts to cultivate black cumin in Indonesia, especially in sub-optimal land as initial information in the field of plant adaptation studies. This study aimed to determine the effect of manure on yield components and bioactive content of black cumin in the ultisol lowland of Bengkulu. The study was conducted at Dehasen Bengkulu University research station at an altitude below 100 m above sea level. The accessions of India, Syria, and Kuwait were used at the main plot, whereas media for growing viz cow manure, chicken manure, and without manure as a subplot. The study was conducted in February 2019 using the Split Plot Design with three replications. Observations were made on the components of yields and bioactive levels of seeds. The results showed that the application of chicken manure increased the components of the yield of black cumin seed by parameter number of capsules per plant, number of seeds per capsule, and number of seeds per plant and tended to reduce the weight of 1000 seeds. An increasing level of thymoquinone in the cultivation of black cumin in ultisol lowland of Bengkulu was obtained in the cow manure application. The increased levels of seed thymoquinone were accompanied by decreased levels of thymol for all accession used.